Leksikon Etnobotani Bahasa Jawa - Suhandono Suhandono; M. Ramlan; Soepomo Poedjosoedarmo; Heddy Shri Ahimsa- Putra (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2004)
Language reflects human conceptualization, human interpretation of the world. This paper describe lexicon ethnobotany in Javanese term of the Javanese speakers' conceptualization/ interpretation of the plants world. In this paper the ethnobotanical lexicons in Javanese are also analyzed in terms of the general principles of ethnobotanical lexicons across languages.